The reality of applying servant leadership behaviors in Palestinian universities "An applied study on Al-Aqsa University" - El-Sawalhy, Emad Youniss; Abadsa, Shaimaa Jamel; Al-Shaer, Yasmeen Sameer; Meqdad, Shaima Ahmed; Aqel, Abdullah Mohammed Ali (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the reality of the application of servant leadership behaviors in Palestinian universities through an applied study on administrative staff working at Al-Aqsa University, (170) questionnaires were distributed to the study population of (302) employees using the simple random sampling method, and (169) questionnaires were retrieved with a response rate of 99.41%, and the (SPSS) statistical program was used to analyze the data, the study found that the degree of officials’ practice of servant leadership at Al-Aqsa University was high, (73.38%), and the university officials were keen on equal authority and responsibility when delegating some powers to subordinates. The study recommended working on implementing training programs for officials to develop their skills and knowledge about the features of servant leadership and its benefits and impact on both the university and the employees, and working on developing the relationship between leaders and subordinates through intensifying meetings and meetings and opening the way for subordinates to express their views and opinions and discuss them transparently and objectively.
Keywords: Leadership; servant leadership; Al-Aqsa University; leadership strategies; Palestinian universities